Lu–Hf isotopic systematics of zircon from lower crustal xenoliths in the Belomorian mobile belt - Vetrin, V. R.; Belousova, E. A.; Kremenetsky, A. A. (Geology of Ore Deposits, 2018)
The structure, geochemistry, and U–Pb and Lu–Hf isotopic composition of zircon crystals from garnet granulite xenoliths of the lower crust in the Belomorian mobile belt have been studied. It has been established that Early Paleoproterozoic zircon, 2.47 Ga in age, is primary magmatic and formed during crystallization of mafic rocks in the lower crust. Meso- and Neoarchean zircons are xenogenic crystals trapped by mafic melt during its contamination with older crustal sialic rocks. Metamorphic zircon grains have yielded a Late Paleoproterozoic age (1.75 Ga). A Paleozoic age has been established for a magmatic crystal formed due to interaction of xenoliths with an alkaline ultramafic melt, which delivered xenoliths to surface. The U–Pb datings and Lu–Hf systematics of crystals have been used to delineate the stages of formation and transformation of the lower crust in this region.